Pembelajaran Realistic Mathematics Education (RME) Berbasis Literasi Numerasi: Setrategi dan Tantangan - Nurwahid; Sofia Ashar; Annafi Awantagusnik (CONSISTAN (Jurnal Tadris Matematika), 2025)
This study aims to identify the implementation strategies and challenges faced in applying the Realistic Mathematics Education (RME) approach based on numeracy literacy mathematics learning. A systematic literature review method was employed, analyzing scholarly articles published between 2018 and 2024. The findings reveal that the main strategies in RME-based numeracy literacy include the use of realistic contexts, mathematical modeling, scaffolding, group discussions, and individual reflection. These strategies positively contribute to students’ conceptual understanding and numeracy skills. However, several challenges were also identified, such as limited teacher comprehension of RME philosophy, lack of contextual learning resources, and resistance to shifting from traditional teaching methods. These findings have significant implications for teacher training, the development of contextual teaching materials, and education policies that support numeracy literacy. The study concludes that the success of RME implementation heavily depends on the readiness of the educational ecosystem to support meaningful and contextual learning.